SketchMeNomics / Anis Ajaereah Mohammad Mokhtar … [et al.] - Mohammad Mokhtar, Anis Ajaereah; Muhamad, Siti Zulbaidah; Ahmad, Muhammad Hafiz Azizi; Muhamad Noor, Nurshahida Azra; Zakaria, Nur Alifah; Abu Hassan Asari, Fadli Fizari (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Mind map could probably be the most unique innovation in teaching and learning as it combines creativity and effectiveness in enabling us to compile a lot of information and summarizes them all into a unique point of study. Taking Managerial Economics (M.E) as an example, it is a subject that contains three components namely, mathematics, business and microeconomics. Students will understand in-depth about the business world from both mathematics and microeconomics perspective as an outcome of this subject. This innovation will introduce the students to an easy and simple technique to understand the M.E by using the mind map concept. Therefore, the main objective of this innovation is to simplify the learning and teaching process. Compared to other mind maps, SketchMeNomics applies the "mirror" concept that explains how the left part can reflect the right part, especially for chapter four and chapter five. At the same time, this mind map also highlights other chapters which are contained in the syllabus. In addition, this product can be commercialized to support the teaching and learning process effectively. In a nutshell, it is hoped that this innovation can be commercialized and used by others in learning M.E. in an easier way